2015
DOI: 10.1002/ppul.23246
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disordered breathing and sleep quality in children with bronchiolitis obliterans

Abstract: The incidence of sleep-disordered breathing (SDB) increases in chronic lung diseases. Our aim was to evaluate SDB and sleep quality in children with postinfectious bronchiolitis obliterans (BO) and assess associated risk factors. We hypothesized that children with BO are at increased risk for SDB and have impaired sleep quality. We also hypothesized that severity of SDB and impairment of sleep quality is related to the severity of lung disease. Sleep Related Breathing Disorder (SRBD) subscale of the Pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Then again, as far as we know, there is no sleep quality index for which Turkish validity and reliability study has been conducted for children and this index has been used in several articles to assess sleep quality of Turkish children. [39,40] Thus, PSQI was preferred in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Then again, as far as we know, there is no sleep quality index for which Turkish validity and reliability study has been conducted for children and this index has been used in several articles to assess sleep quality of Turkish children. [39,40] Thus, PSQI was preferred in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…5, 28 The measure has been used successfully in children with health problems as young as 8-years of age, 2, 4, 40 and has been validated in children as young as age 14-years, with one small variation to a single question that makes reference to driving. 9 …”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that a study analysing sleepdisordered breathing in children with PIBO showed that the risk of nocturnal hypoxia was increased in patients with PIBO and it was correlated with the severity of lung disease determined by pulmonary function test. While the duration of central apnoeas was shorter, they were more prone to desaturations [63].…”
mentioning
confidence: 90%